Narrating the globe : the emergence of world histories of architecture, 1790-1900 - Brouwer, Petra; Bressani, Martin; Armstrong, Christopher Drew (Cambridge, Massachusetts : The MIT Press, 2023)
"An anthology of writings by assorted scholars, accompanied by a lot of original archival illustrations, promoting a new and explicitly global history of largely nineteenth-century architecture"--
Thematic essays -- Monographic studies of key world histories of architecture -- Twenty-first century perspectives on world architectural history.
boek